The effect of different dietary levels of energy and protein on the production and body composition of broiler breeders - Du Plessis, J. J. P. (Johannes Jacobus Pieter) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2000